The Effect of Asthma and Acute Respiratory Infections in Childhood on Educational Attainment in Indonesia - Shelby Devianty Widodo; Mohammad Khaerul Azis (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2022)
Asthma and Acute Respiratory Infections (ARI) is one of the most chronic respiratory diseases children suffer. According to the Global Initiative for Asthma (GINA) in 2018, the prevalence rate of asthma is between 1-18 percent of the total population in each country. This study aims to analyze the effect of childhood-asthma and ARI history on educational attainment. We use data from Indonesia Family Life Survey (IFLS) wave 1993 and 2014. The Ordinary Least Square (OLS) regression method was used to assess that effect. The results indicate childhood-asthma and ARI history do not affect a person’s educational attainment in adulthood.How to Cite:Widodo, Shelby D., & Azis, Muhammad K., (2022). The Effect of Asthma and Acute Respiratory Infections in Childhood On Educational Attainment In Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 11(1), 191-200. https://doi.org/10.15408/sjie.v11i1.13549.